Characterisation of Bidor Kaolinite and Illite - Liew, Kong Yong; Khoo, Lean E.; Bong, K. T. (1985)
Two types of commercial clay minerals from the Bidor region of Perak were studied. From the X-ray diffraction study, these clays were identified as disordered kaolinite and 2 M polymorph of illite. The morphologies, the surface properties, the pore structures and the infrared absorption properties were examined. The basis for the identification of these clays is discussed.